Plant-mediated synthesis of zinc oxide and copper oxide nanoparticles by using ferulago angulata (schlecht) boiss extract and comparison of their photocatalytic degradation of Rhodamine B (RhB) under visible light irradiation - Shayegan Mehr, Ebrahim; Sorbiun, Mina; Ramazani, Ali; Taghavi Fardood, Saeid (Journal of materials science. Materials in electronics, 2018)
In this work, we have reported, a cost effective and environment friendly technique for the synthesis of ZnO and CuO nanoparticles using ferulago angulata (schlecht) boiss extract as a mild and non-toxic reducing agent and efficient stabilizer without adding any surfactants. The secondary metabolites, ubiquitously found in plants have a significant role in synthesis of nanoparticles. As-synthesized metal oxides nanoparticles were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, field emission-scanning electron microscopy. X-ray diffraction results revealed that the biosynthesized ZnO NPs and CuO NPs were crystalline in nature with higher purity and particle size of ~ 44 nm. In addition, the photocatalytic degradation activity of ZnO and CuO photocatalyst were evaluated using Rhodamine B as organic contaminant irradiated only with visible light from fluorescent lamp. Catalytic reactions were monitored by using UV–Vis spectrophotometer. This study indicates photocatalytic degradation capacity of the ZnO NPs was higher than CuO NPs.